Characterization of Antibacterial Protein from Hemolymph of Oyster Crassostrea belcheri - Nuchchanart, Wirawan; Poompuang, Supawadee; Tunkijjanukij, Suriyan; Nakasathien, Sutkhet (Agriculture and Natural Resources, 2007)
The hemolymph of oyster Crassostrea belcheri was found to possess significant antibacterial activity against Vibrio harveyi, V. vulnificus and V. cholerae. Hemolymph was partially purified by gel filtration chromatography on Sephacryl S-200 and fractioned into four parts: P1, P2, P3 and P4. The P3 showed the highest antibacterial activity against V. parahaemolyticus, V. cholerae, V. alginolyticus, V. harveyi in the inhibition ranges from 95-62% and V. vulnificus was inhibited only 8% with 64 mg protein. The antibacterial activity of P3 protein was stabilized at pH 6-8 and 4-30°C. In addition, the activity required calcium ion. Molecular weight of the antibacterial protein P3 determined by gel filtration was approximately 18.7 kDa. Antibacterial protein gave two bands of 25.0 and 30.5 kDa in SDS-PAGE and pI was 3.0 and 5.0, respectively. Both bands were analyzed by LC-MS/MS and compared with nrFasta database. The 30.5 kDa band was homologous to hemocyte extracellular superoxide dismutase from C. gigas and 25.0 kDa band was homologous to sarcoplasmic calcium-binding protein.